Internalization of Indonesian Economic Ideology on Formal Education for Elementary School Level - Eunike Rose Mita Lukiani; Ery Tri Djatmika Rudijanto Wahju Wardhana; Agus Suman; Hari Wahyono (Qubahan Academic Journal)
This research aims to internalize and indoctrinate Indonesian economic ideology through economic learning for elementary school students and also test the effectiveness of economic learning tools based on the Articles of the 1945 Constitution. This research applied a Design Based Research (DBR) development research approach. The results of this research are economic learning development products based on articles of the 1945’s Constitution which are based on joint efforts based on the principle of kinship, which can effectively indoctrinate and internalize elementary school students in the economic ideology of the Indonesian nation. This process is carried out by instilling Indonesian economic ideology from an early age, students can know, recognize and have the character of the values of Indonesian economic ideology in their lives.